Homework #6

# Homework #6 - jiwani (amj566) – Homework06 – Fouli –...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: jiwani (amj566) – Homework06 – Fouli – (58395) 1 This print-out should have 16 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. 001 10.0 points Find the derivative of f when f ( x ) = 4 x cos 3 x- 2 sin 3 x . 1. f ′ ( x ) =- 6 cos 3 x + 12 x sin 3 x 2. f ′ ( x ) = 12 x sin 3 x- 2 cos3 x 3. f ′ ( x ) = 6 cos 3 x- 2 x sin 3 x 4. f ′ ( x ) =- 12 x sin3 x- 2 cos 3 x correct 5. f ′ ( x ) =- 12 x sin3 x- 6 cos3 x Explanation: Using formulas for the derivatives of sine and cosine together with the Product and Chain Rules, we see that f ′ ( x ) = 4 cos 3 x- 12 x sin3 x- 6 cos3 x =- 12 x sin 3 x- 2 cos 3 x . 002 10.0 points Determine f ′ ( x ) when f ( x ) = x- 1 √ x 2- 2 . 1. f ′ ( x ) = 2 + x ( x 2- 2) 3 / 2 2. f ′ ( x ) = x- 2 ( x 2- 2) 1 / 2 3. f ′ ( x ) = 2- x ( x 2- 2) 3 / 2 4. f ′ ( x ) = x- 2 ( x 2- 2) 3 / 2 correct 5. f ′ ( x ) = x + 2 ( x 2- 2) 1 / 2 6. f ′ ( x ) = 2- x ( x 2- 2) 1 / 2 Explanation: By the Product and Chain Rules, f ′ ( x ) = 1 ( x 2- 2) 1 / 2- 2 x ( x- 1) 2( x 2- 2) 3 / 2 = ( x 2- 2)- x ( x- 1) ( x 2- 2) 3 / 2 . Consequently, f ′ ( x ) = x- 2 ( x 2- 2) 3 / 2 . (Note: the Quotient Rule could have been used, but it’s simpler to use the Product Rule.) 003 10.0 points Find the derivative of y when y = 6 sin √ x- 8 √ x cos √ x . 1. y ′ = 4 sin √ x- cos √ x √ x correct 2. y ′ = 4 cos √ x- 7 parenleftBig sin √ x √ x parenrightBig 3. y ′ = 4 sin √ x- 7 parenleftBig cos √ x √ x parenrightBig 4. y ′ = 3 sin √ x + cos √ x √ x 5. y ′ = 3 sin √ x + 7 parenleftBig sin √ x √ x parenrightBig 6. y ′ = 3 cos √ x + sin √ x √ x Explanation: jiwani (amj566) – Homework06 – Fouli – (58395) 2 By the Product and Chain Rules, y ′ = 3 parenleftBig cos √ x √ x parenrightBig- 4 parenleftBig cos √ x √ x parenrightBig + 4 parenleftBig √ x sin √ x √ x parenrightBig . Consequently, y ′ = 4 sin √ x- cos √ x √ x . 004 10.0 points Find the derivative of f when f ( x ) = parenleftBig 4 x 3 / 2- x − 3 / 2 parenrightBig 2 . 1. f ′ ( x ) = 4 parenleftbigg 16 x 6 + 1 x 4 parenrightbigg 2. f ′ ( x ) = 3 parenleftbigg 4 x 3 + 1 x 3 parenrightbigg 3. f ′ ( x ) = 4 parenleftbigg 16 + x − 6 x 3 parenrightbigg 4. f ′ ( x ) = 3 parenleftbigg 4 x 6- 1 x 3 parenrightbigg 5. f ′ ( x ) = 3 parenleftbigg 16 x 6- 1 x 4 parenrightbigg correct 6. f ′ ( x ) = 4 parenleftbigg 16- x − 6 x...
View Full Document

## This note was uploaded on 07/10/2011 for the course KIN 321M taught by Professor Jensen during the Spring '11 term at University of Texas.

### Page1 / 7

Homework #6 - jiwani (amj566) – Homework06 – Fouli –...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online